Penatalaksanaan Fisioterapi Pada Kasus Oateoartritis Dengan Modalitas Infra Red Dan Terapi Latihan - Violin Sabatina; Liza Agustin (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Osteoarthritis is a degenerative disease of the joints that involves cartilage, joint lining, ligaments, and bones, causing pain and stiffness in the joints that occur due to chronic disorders of the joints and bones. The purpose of this study was to determine the management of physiotherapy and the benefits in cases of Osteoarthritis with infrared and exercise therapy in reducing, increasing joint range of motion and increasing muscle strength in patients with osteoarthritis. After performing therapeutic actions for 6 times the following results were obtained: at T1 the decrease in the degree of silent pain was 3 and at T6: reduced to 2, motion pain at T1 was 4 and at T6 it became 3. Then for muscle strength which was initially T1: 3 and at T6 to 4. Conclusion, In the case of Osteoarthritis with infrared modalities and exercise therapy can reduce pain, increase muscle strength.Keywords: Osteoarthritis, infrared, exercise therapy